126 The Theatre Training Checklist: A Toolkit to Improve Operative Training. (28th February 2022) - Aldoori, J.; Burke, J.; Robson, A.; Al-Attar, A.; Giwa, L.; O'Regan, D.; Peter, M.
Abstract: Aim: The operating theatre is expensive, costing approximately £1200 per hour to run. It is a crucial learning environment for many different trainees: anaesthetists, surgeons, operation department practitioners, etc. For individuals to achieve their training requirements, the operating theatre as a training environment must be shared between all trainees, requiring excellent teamwork and leadership. This could be improved by the adoption of innovative training strategies. Method: The Theatre Training Checklist is a simple framework that aims to facilitate awareness, understanding, coordination and cooperation of training for all team members. It is a practical strategy that can be adopted in any setting. Usually, trainers discuss informally with their trainees about their individual skills, experience, expectations and what is achievable in a theatre list. However, there is currently limited opportunity to discuss this between different disciplines and the wider team. This tool aims to refine communication, optimize training, manage expectations, and ensure equity across the board. Results: The checklist is completed at the start of the list during the theatre brief. It identifies all trainees and their specific needs within the operating theatre session to the whole team. An agreed strategy is developed on how to achieve identified training goals. Feedback undertaken from the MDT after local trailing of the checklist has been positive. Conclusions: The toolkit is available for use and consists of the checklist tool and an instructional video. The checklist is being piloted in some centres and we hope to have the opportunity to present some early findings to the ASiT Innovation Summit.